STUDENT LEARNING ACHIEVEMENT MODEL: LEARNING MOTIVATION AND LEARNING INTEREST WITH PARENTS' ATTENTION AS INTERVENING VARIABLES (Jurnal Ipteks Terapan, 2022)
The aim of this study was to examine the extent to which the influence learning motivation and interest in learning have on student achievement with parental attention as an intervening variable. Method collection data through survey and spread questionnaire, with a sample of 100 respondents obtained by the saturated sample formula at The population of the UPI YPTK campus is 100. The analytical method used is the inner model and path coefficients. Results study which obtained based on path coefficients obtained: 1) None influence positive which significant motivation to learn to student learning achievement significant value 0.994 0.05. 3) None influence positive which significant motivation to learn to parents attention where significant value 0.063